Basic insights into Zika virus infection of neuroglial and brain endothelial cells. (30th June 2020) - Mutso, Margit; St John, James A.; Ling, Zheng Lung; Burt, Felicity J.; Poo, Yee Suan; Liu, Xiang; Žusinaite, Eva; Grau, Georges E.; Hueston, Linda; Merits, Andres; King, Nicholas J.C.; Ekberg, Jenny A.K.; et al.
Abstract : Zika virus (ZIKV) has recently emerged as an important human pathogen due to the strong evidence that it causes disease of the central nervous system, particularly microcephaly and Guillain–Barré syndrome. The pathogenesis of disease, including mechanisms of neuroinvasion, may include both invasion via the blood–brain barrier and via peripheral (including cranial) nerves. Cellular responses to infection are also poorly understood. This study characterizes the in vitro infection of laboratory-adapted ZIKV African MR766 and two Asian strains of (1) brain endothelial cells (hCMEC/D3 cell line) and (2) olfactory ensheathing cells (OECs) (the neuroglia populating cranial nerve I and the olfactory bulb; both human and mouse OEC lines) in comparison to kidney epithelial cells (Vero cells, in which ZIKV infection is well characterized). Readouts included infection kinetics, intracellular virus localization, viral persistence and cytokine responses. Although not as high as in Vero cells, viral titres exceeded 10 4  plaque-forming units (p.f.u.) ml −1 in the endothelial/neuroglial cell types, except hOECs. Despite these substantial titres, a relatively small proportion of neuroglial cells were primarily infected. Immunolabelling of infected cells revealed localization of the ZIKV envelope and NS3 proteins in the cytoplasm; NS3 staining overlapped with that of dsRNA replication intermediate and the endoplasmic reticulum (ER). Infected OECs and endothelial cells produced high levels of pro-inflammatory chemokines. Nevertheless, ZIKV was also able to establish persistent infection in hOEC and hCMEC/D3 cells. Taken together, these results provide basic insights into ZIKV infection of endothelial and neuroglial cells and will form the basis for further study of ZIKV disease mechanisms.